EDUKASI LINGKUNGAN SEHAT MASA PANDEMI COVID 19 DI KELURAHAN KALIDONI KOTA PALEMBANG - Hakim, Arif Rahman; Bayumi, Ruli Ihsan; Sutinah, Sutinah; Ivana, Ivana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2023)
This community service focuses on the Palembang community environment and is also included in activities with Stisipol Candradimuka Palembang students in Kalidoni Kota Village. There are still people in Kalidoni Village who do not comply with health protocols in implementing 3M (wearing masks, maintaining distance and washing hands). This community service is in collaboration with the Kalidoni Village, Palembang City and the Kalidoni Community Health Center by providing outreach about the importance of creating a healthy environment during the Covid 19 pandemic using focus group discussion methods, and education about Covid-19 prevention protocols and distribution of equipment such as masks, hand sanitizers and education. regarding preventing the transmission of Covid 19. The aim of this community service is to provide knowledge to the community about the Covid 19 pandemic and provide an overview of how to create a healthy environment during the Covid 19 pandemic.